Layer Structured Materials for Advanced Energy Storage and Conversion. Issue 45 (13th September 2017) - Guo, Yanpeng; Wei, Yaqing; Li, Huiqiao; Zhai, Tianyou
Abstract: Owing to the strong in‐plane chemical bonds and weak van der Waals force between adjacent layers, investigations of layer structured materials have long been the hotspots in energy‐related fields. The intrinsic large interlayer space endows them capabilities of guest ion intercalation, fast ion diffusion, and swift charge transfer along the channels. Meanwhile, the well‐maintained in‐plane integrity contributes to exceptional mechanical properties. This anisotropic structural feature is also conducive to effective chemical combination, exfoliation, or self‐assembly into various nanoarchitectures, accompanied by the introduction of defects, lattice strains, and phase transformation. This review starts with a brief introduction of typical layered materials and their crystal structures, then the structural characteristics and structure oriented unique applications in batteries, capacitors, catalysis, flexible devices, etc., are highlighted. It is surprising to observe that layered materials possess: (1) high reactivity, high reversibility, and enhanced performance via forming additional chemical bonds in alkali‐metal ion batteries; (2) facile phase modulation, great feasibility for in‐plane/sandwich device design, and cation intercalation enabled high capacitance in supercapacitors; (3) promoted structural diversity, effective strain engineering, and capabilities to function as ideal supporting materials/templates in electrocatalysis field. Finally, the future prospects and challenges faced by layered materials are also outlined. Abstract : The strong in‐plane chemical bonds and weak van der Waals force between adjacent layers endow layer structured materials with large interlayer space and capabilities of space modulation, high in‐plane conductivity, considerable active sites, abilities of effective exfoliation and defect/phase/strain engineering. Moreover, they exhibit superior mechanical properties, leading to unique performances in batteries, supercapacitors, catalysis, flexible devices, etc.